POSITION OF INFORMED CONSENT IN EMERGENCY HANDLING OF PATIENTS IN HOSPITAL - Zulkarnain, Hadi; Hoesein, Zainal Arifin (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
The Indonesian Constitution mandates that health must be the main thing in continuous sustainable development. Therefore, in order to create a good health law system, doctors must respect whatever the patient's choice is, because if informed consent has occurred, then the rights and obligations between the doctor and the patient arise. However, the position of informed consent becomes unclear when there is emergency treatment of patients in hospitals. The problem studied is how is the position of informed consent in emergency treatment of patients in hospitals in law in Indonesia and the United States? The research method used is normative. The results of the study show that the position of informed consent in emergency treatment of patients in hospitals in law in Indonesia and the United States is different. In the health law system in Indonesia, the position of informed consent in emergency treatment of patients in hospitals is considered given, so that doctors who perform medical actions in order to save lives or prevent disability of a person in an Emergency and/or disaster are exempt from claims for compensation. A different thing happens in the health legal system in the United States, where the position of informed consent in emergency patient care in hospitals remains very important in law, because the legal consequences if informed consent is not given, are that the medical action is considered an act of abuse (intentionally) against the patient which causes the doctor and hospital to become parties who can be held legally responsible if the patient feels disadvantaged.